A Sosialisasi Aman Bermedia Sosial: - - Eceh Trisna Trisna Ayuh; Titi Darmi; Faizal Anwar; Linda Safitra; Hafri Yuliani; Rekho Adriadi (Program Studi Administrasi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Muhammadiyah Bengkulu, 2022)
Social media has such a big impact on social life. Web-based media that can turn communication into interactive dialogue and support social interaction. Social media is generally used to share and participate. Some of the most popular social media sites today include Youtube, Facebook, Instagram, What'sapp and others. Apart from being popular among young people, social media is also popular among millennial mothers. The popularity and ease of access to social media has had various impacts, for example when many social media users are always updating information about various kinds of confidential information that does not deserve to be shared with the public but this appears every day. The information distributed also varies, there are users who spread information related to hoax news, important information and hate speech. It can be exploited by certain persons for personal gain. There will be certain individuals who spread issues of conflict, hostility and disappointment towards the government because they are seen as not paying attention to their people. There are also those who distribute videos depicting how bad the government is so that the message is swallowed whole. Meanwhile, the general public will immediately absorb the information presented on social media without finding out the truth. Therefore, the role of social media in managing issues and being safe in social media is really needed as a guide and measure for us to be smart in social media (smartphone people). So that the information contained on social media can make people think positively and take recommended actions to maintain their health. This service research aims to increase the selectivity of the community in receiving information in the era of the rapid flow of information. In the Community Service Research that has been carried out, in essence not all information on social media is in accordance with the facts, so users need to filter it before sharing. As a smart user and who also acts as citizen journalism, he should provide information that is positive, useful, does not contain suggestions, does not trigger conflict and can build unity and unity. Whether or not the use of social media is appropriate depends on its users, whether they can be smart or not. Being a savvy social media user can make social media safety possible.